Sliding genioplasty pada penatalaksanaan deformitas dagu - Edi Supriyanto; Asri Arumsari; Bambang A. Sulthana (DiscoverSys Inc., 2009)
Chin contour and position is important component in facial balance. Deformities ofchin may occur as isolation deformity or associated with other dentofacialdeformities. This is a case report of 15-year old girl with chief complaint of chindeformity, and sliding genioplasty has been performed without any complication.